Removal of casting defects from CMSX-4® and CMSX-10® alloys by electropolishing in a novel electrolyte; Deep Eutectic Solvent - Dsouza Neil; Appleton Matthew; Ballantyne Andrew; Cook Amy; Harris Robert; Ryder Karl S. (MATEC Web of Conferences, 2014)
Here we describe the use of environmentally benign Deep Eutectic Solvents (DESs) to electropolish oxide casting scale from Ni based superalloy turbine blades. These new electrolytes are a viable alternative to hazardous and aggressive aqueous acids and etchants currently used to process these components. In addition we show that the DES electrolytes selectively expose the underlying surface structure of these superalloys. We demonstrate the ability of these electrolytes to preferentially etch either γ or γ′ phases depending on the choice of electrolyte formulation and the applied potential during the electrolytic etch on CMSX-4® and CMSX-10® alloys.